The development and performance evaluation of Particle Filter–H∞ Filter for attitude estimation of a small satellite in low earth orbit - Aman, Asma Mohammad Nusrat (2023)
The accurate determination of the attitude of small satellites is essential for missions with stringent pointing requirements. Small satellites such as CubeSats are subject to mass and volume constraints, which directly affects their ability to carry more extensive and demanding payloads and limits their power and computational capabilities. There is, therefore, a need to minimise the computational cost of attitude determination while maximising accuracy and robustness to make small satellites useful for a wide range of applications. This research investigates the use of low-cost commercial sensors for attitude determination, namely the three-axis magnetometer and sun sensors, and proposes a novel hybrid Particle Filter–H∞ Filter to facilitate higher performance in the attitude determination of CubeSats. Existing attitude determination methods based on Kalman Filters are often not robust enough, which reduces their estimation accuracy, and they are limited in their inability to handle non-Gaussian noise. While Particle Filters offer higher estimation accuracy and the ability to handle non-Gaussian noise, their high computational cost is a distinct disadvantage. This research focuses on the development of a novel attitude estimator, the Particle Filter–H∞ Filter, which aims to achieve high estimation accuracy, robustness and lower computational cost by incorporating an H∞ Filter into the resampling step of a Particle Filter.